2018
DOI: 10.1038/s41598-018-31119-9
|View full text |Cite
|
Sign up to set email alerts
|

Mass screening for liver cancer: results from a demonstration screening project in Zhongshan City, China

Abstract: Current Chinese national guidelines recommend routine screening for liver cancer in patients positive for HBsAg, irrespective of fibrosis status, age, or family history of liver cancer. We aim to evaluate whether the recommended screening strategy could reduce liver-cancer-specific mortality. We conducted a liver cancer mass screening trial in Xiaolan Town, Zhongshan City, China, among residents aged 35–64 years in 2012. All volunteers were offered serological testing for hepatitis B virus surface antigen (HBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…In addition, simple and novel technologies for early detection are also in great need in China, such as self‐sampling for cervical cancer screening [28], although the acceptance was previously observed as being low, more emphasis should be placed on such technologies. Data from the National Cancer Registry of China (NCCRC) showed that cancer survival increased substantially for the overall combined cancers from 2003 to 2015 [29], which could be partly attributed to the implementation of mass screening, although the effectiveness of screening on liver cancer was unclear [30‐32]. Other reasons to improve cancer survival may include improvements in the health care system and New Cooperative Medical Scheme [33‐35].…”
Section: Figurementioning
confidence: 99%
“…In addition, simple and novel technologies for early detection are also in great need in China, such as self‐sampling for cervical cancer screening [28], although the acceptance was previously observed as being low, more emphasis should be placed on such technologies. Data from the National Cancer Registry of China (NCCRC) showed that cancer survival increased substantially for the overall combined cancers from 2003 to 2015 [29], which could be partly attributed to the implementation of mass screening, although the effectiveness of screening on liver cancer was unclear [30‐32]. Other reasons to improve cancer survival may include improvements in the health care system and New Cooperative Medical Scheme [33‐35].…”
Section: Figurementioning
confidence: 99%
“…This finding shows that the screening of individuals at highrisk with semiannual AFP and US detection is effective not only in increasing detection rate of early stage liver cancer but also in improving patients' survival. Ji et al [102] reported another example from Zhongshan, Guangdong Province that started in 2012.…”
Section: Recent Advances In Screening From 2 Rural Areasmentioning
confidence: 99%
“…Although there is currently no internationally recognized program for the screening for liver cancer, except for some aspects of the consensus, in the past decades China has experienced many screening trials [15,19,20,90,93,97,100,102] , which have fully demonstrated the Chinese characteristics (most patients are HBV-related liver cancer) and the need for the management and control for the one of its most common malignancies. Professional societies in Western countries had proposed recommendations and guidelines on this special issue [108] , although in the recent American Cancer Society Guidelines, the screening for liver cancer is not mentioned [133] .…”
Section: Prospects For Liver Cancer Screeningmentioning
confidence: 99%
“…Another recent community-based trial among patients with positive chronic hepatitis B in China found that participation in ultrasound-based surveillance improved early tumour detection and survival but did not reduce HCC-related mortality. 44 Although a clear mortality benefit has not been demonstrated, routine HCC surveillance generally fulfils criteria for a successful screening program: there are two easily identified populations that are at high risk; the tumour usually has a long latent preclinical phase detectable with imaging, and curative treatments are feasible if diagnosed at an early stage; and surveillance with ultrasound is an acceptable, low-risk technique with an overall sensitivity of 84% for all HCCs and 47% for early HCC, as demonstrated by meta-analysis. 45 The reason surveillance has not had a clear impact on HCC mortality is complex.…”
Section: Opportunities For Lynch Syndrome Testingmentioning
confidence: 99%